Bishop as witness of charity. Canonical profile - INTERGUGLIELMI, ANTONIO (Prawo Kanoniczne, 2017)
The diocesan Bishop governs the particular Church entrusted to him with legislative, executive and judicial power (can. 391 § 1), as well as through the exercise of his pastoral office, he, the Bishop is the first on which looms this charitable mission. It is a juridical requirement of the Bishop that the code of canon law and the documents of the Magisterium treat several times, from a pastoral point of view. It is, in fact, inherent in the task of guiding the particular Church entrusted to him and guarantor of the ecclesial spirit, that the Bishop orients towards charity the action of priests, the faithful and associations of the Church (can. 318 § 1), showing the attention to the poor and needy of the portion of the people of God that he presides. This supporting role towards charity, the Bishop may exercise through the diocesan councils which he presides: the Diocesan Council for the Economic Affairs (can. 492), the Diocesan Pastoral Council and eventually other Diocesan organisms that could be constituted for this end, such as Caritas, organizations that must be created both, at the level of parishes, and other entities that are part of the head of the diocese (can. 1280). The supervision of the management of the goods that competes to the diocesan Bishop in the light of the rules and of the Magisterium, should then be understood not only as a mere work of control, but also as a core function in the field of administration of the goods for realising that “attention to the poorest”, which is part of the practice of the Church’s mission.